Restored Karst Areas: A Multi-Case Study of Community-Based Conservation in Gunungkidul - Ali Hidayat Fatmayanto; Suharko Suharko (Departemen Sosiologi Universitas Gadjah Mada, 2025)
This study underscores the importance of conservation movements, which relies on local knowledge to sustain the environment and enhance community welfare, by examining the Resan Gunungkidul Community as a representative case from Indonesia’s Gunungsewu Karst Landscape. We using qualitative descriptive methods through multi-case approaches, and the data were collected through in-depth interviews and participatory observations with some communities in field. This study analyzes the KRG's educating strategies for common pool resource management with any local movements. The results of the study confirmed that KRG successfully developed a conservation model in the name “resan”. That conservation model through the use of a broad social network, the application of a common-pool resources (CPR) approach, and the horizontal leaders. The emergence of KRG does not only affect its core movement, but also significantly impacts the development of other communities. Even with limitations, such as a small scale of action, low member flexibility, limited segmentation, and minimal financial resources, KRG was able to maintain local conservation movements. Their educating innovations boosted biodiversity, improved pest monitoring, expanded conservation knowledge, and strengthened collaboration networks. This study highlights that multidisciplinary engagement and the application of similar models in other contexts are essential to strengthen the impact of community-based conservation in ecologically vulnerable areas.